On the Hypolipidemic Activity of Elicited Soybeans: Evidences Based on Computational Analysis - Feri Eko Hermanto; Warsito Warsito; Muhaimin Rifa'i; Nashi Widodo (Universitas Gadjah Mada, 2022)
Dietary intervention plays a significant role in regulating hyperlipidemia. Besides, elicited soybean has greater bioactive contents with numerous health benefits potential. However, there is no evidence of the hypolipidemic activity of elicited soybean. This study will explore the potential mechanism of hypolipidemic activity of bioactive compounds from elicited soybean through computational modeling. The phytocompounds from elicited soybean were identified by Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS), then screened for potential toxicity and drug-likeness properties. Compounds with low potential toxicity and excellent drug-likeness properties were screened for hypolipidemic activity against 3-Hydroxy-3-Methylglutaryl-CoA Reductase (HMGCR) and Peroxisome Proliferator Activator Receptor-gamma (PPAR-γ) through molecular docking coupled with molecular dynamics. The result showed that phytocompounds from the isoflavonoid group have an excellent affinity to bind with the HMGCR and PPAR-γ. Daidzein, Genistein, and Glycitein interacted with the catalytic residues of HMGCR to act as potential inhibitors with great affinity and stability. Genistein and Glycitein showed strong affinity and stability during their interaction with the agonistic sites of PPAR-γ. Further, the protein network described that targeting HMGCR inhibitor and PPAR-γ had the advantage in orchestrating cholesterol metabolism homeostasis. In summary, isoflavonoids from elicited soybean may have hypolipidemic activity through HMGCR inhibition and PPAR-γ activation.